Human Capital Development and Financial Sector Efficiency: Drivers of International Trade Competitiveness in Sub-Saharan Africa - Danquah, David Aboagye; Tsaurai, Kunofiwa (Acta Universitatis Danubius. Œconomica, 2024)
This study assesses the relationship between human capital development, financial sector efficiency, and international trade competitiveness in Sub-Saharan Africa (SSA). The study utilised the system Generalised Moment Method (GMM) to analyse annual panel data for 38 SSA economies from 1980 to 2022. The study revealed human capital development serves as a channel for financial development to impact trade. Thus, for each unit increase in the interaction between financial development and human capital development, trade intensity increases by approximately 0.412%. and trade volume increases by approximately 0.4507%. The study suggests that policymakers in Sub-Saharan Africa should integrate financial literacy and managerial skills training to enhance international trade competitiveness, focusing on SMEs, while also facilitating SME access to financial services, establishing funding mechanisms, and strengthening institutional support for trade promotion, to foster sustainable growth in trade intensity and volume.